Renal complications of lipodystrophy: A closer look at the natural history of kidney disease. (17th May 2018) - Akinci, Baris; Unlu, Sadiye Mehtat; Celik, Ali; Simsir, Ilgin Yildirim; Sen, Sait; Nur, Banu; Keskin, Fatma Ela; Ozgen Saydam, Basak; Kutbay Ozdemir, Nilufer; Sarer Yurekli, Banu; Ergur, Bekir Ugur; Sonmez, Melda; et al.
Summary: Objectives: Lipodystrophy syndromes are a group of heterogeneous disorders characterized by adipose tissue loss. Proteinuria is a remarkable finding in previous reports. Study design: In this multicentre study, prospective follow‐up data were collected from 103 subjects with non‐HIV‐associated lipodystrophy registered in the Turkish Lipodystrophy Study Group database to study renal complications in treatment naïve patients with lipodystrophy. Methods: Main outcome measures included ascertainment of chronic kidney disease (CKD) by studying the level of proteinuria and the estimated glomerular filtration rate (eGFR). Kidney volume was measured. Percutaneous renal biopsies were performed in 9 patients. Results: Seventeen of 37 patients with generalized and 29 of 66 patients with partial lipodystrophy had CKD characterized by proteinuria, of those 12 progressed to renal failure subsequently. The onset of renal complications was significantly earlier in patients with generalized lipodystrophy. Patients with CKD were older and more insulin resistant and had worse metabolic control. Increased kidney volume was associated with poor metabolic control and suppressed leptin levels. Renal biopsies revealed thickening of glomerular basal membranes, mesangial matrix abnormalities, podocyte injury, focal segmental sclerosis, ischaemic changes and tubular abnormalities at various levels. Lipid vacuoles were visualized in electron microscopy images. Conclusions: CKD is conspicuously frequent in patients with lipodystrophy which has an early onset. Renal involvement appears multifactorial. While poorly controlled diabetes caused by severe insulin resistance may drive the disease in some cases, inherent underlying genetic defects may also lead to cell autonomous mechanisms contributory to the pathogenesis of kidney disease.